AKTIVITAS PEMBELAJARAN SEBAGAI SUATU SISTEM - A. Qomarudin (Piwulang: Jurnal Pendidikan Agama Islam, 2021)
Education is an effort to develop the potential of students in the learning environment. So that in achieving these educational goals, it will not be separated from a good learning system. So it is necessary to understand that: learning activities are a unified whole (system) to achieve an expected goal; there are components of the learning system which broadly consist of input, process, output-outcome, and specifically consist of objectives, materials, methods, media, evaluation; There are several factors that influence the learning system, namely the factors of educators, students, infrastructure, and learning environment.